2020
DOI: 10.1177/1740774520956969
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic recruitment methods in a clinical trial of adults with gout

Abstract: Background/aims: Electronic-based recruitment methods are increasingly utilized in clinical trials to recruit and enroll research participants. The cost-effectiveness of electronic-based methods and impact on sample generalizability is unknown. We compared recruitment yields, cost-effectiveness, and demographic characteristics across several electronic and traditional recruitment methods. Methods: We analyzed data from the diet gout trial recruitment campaign. The diet gout trial was a randomized, controlled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17] The inadequate representation of underrepresented populations in clinical trials may have also led to a lack of understanding of the effect of these factors on acceptance of treatment and resultant healthcare inequities. 18 Second, we observed that the social support system appears to be associated with the decision to accept or decline monoclonal antibody therapies. Social capital may be defined as how reciprocal social networks provide support and opportunities for achievement of mutual goals.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17] The inadequate representation of underrepresented populations in clinical trials may have also led to a lack of understanding of the effect of these factors on acceptance of treatment and resultant healthcare inequities. 18 Second, we observed that the social support system appears to be associated with the decision to accept or decline monoclonal antibody therapies. Social capital may be defined as how reciprocal social networks provide support and opportunities for achievement of mutual goals.…”
Section: Discussionmentioning
confidence: 83%
“… 10 - 17 The inadequate representation of underrepresented populations in clinical trials may have also led to a lack of understanding of the effect of these factors on acceptance of treatment and resultant healthcare inequities. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited by identifying patients with a diagnosis of gout in the Johns Hopkins Medicine medical record, newspaper advertisements, Facebook advertisements, and mass mailings to adults living in the communities surrounding the research center [ 17 ]. After completion of two in-person visits at the Johns Hopkins ProHealth Clinical Research Unit (Woodlawn, Maryland, USA), eligible adults were randomized to one of two 4-week intervention sequences: the provision of DASH-patterned groceries followed by self-directed grocery purchases or self-directed grocery purchases followed by the provision of DASH-patterned groceries.…”
Section: Methodsmentioning
confidence: 99%
“…With electronic medical records (EMR) becoming omnipresent in health care and electronic-based recruitment methods used widely to boost participation in clinical trials, there is a concern that an overreliance on electronic/online technology may diminish access for eligible and interested underrepresented participant populations. In the research funded by the Johns Hopkins Institute for Clinical and Translational Research, a hybrid outreach strategy combining use of EMRs with postal mailings demonstrated enhanced cost-effectiveness and participation of under-represented groups, including Black participants and women [28].…”
Section: Innovationmentioning
confidence: 99%